Calcar femorale variation in extant and fossil hominids: Implications for identifying bipedal locomotion in fossil hominins. Issue 167 (June 2022) - Cazenave, Marine; Kivell, Tracy L.; Pina, Marta; Begun, David R.; Skinner, Matthew M.
Abstract: The calcar femorale is an internal bony structure of the proximal femur considered to be functionally related to bipedal locomotion. Among extant primates, the presence of a calcar femorale has been so far documented in extant humans and Pan and, among extinct hominins, in the Late Miocene Orrorin, in a Pliocene Australopithecus, and in a Middle Pleistocene Homo specimen. Using high-resolution microcomputed tomography, we investigated the occurrence and morphology (i.e., shape, location, and size) of the calcar femorale in an adult sample of extant humans, Pan troglodytes, Gorilla gorilla, Pongo sp., and Papio ursinus . We also investigated for the first time the occurrence and morphology of a calcar femorale in the adult proximal femoral remains of a Late Miocene great ape ( Rudapithecus ) and five Plio-Pleistocene hominins from Southern and Eastern Africa ( Australopithecus and Paranthropus ). We took four measurements: periosteal-to-tip maximum length, maximum length excluding cortical thickness, maximum vertical height, and the distance between the most anterior and posterior limits of the root. To allow for intergeneric comparisons, estimated body size was used to standardize all measurements. Nine of 10 extant humans have a well-developed calcar femorale. Among the African apes, 6 of 10 Pan and 6 of 10 Gorilla also show a distinct calcar femorale. In Pongo ( n = 9), it is only present in one captive individual. None of the five investigated Papio specimens show any trace of this structure. Only calcar femorale height, which is systematically taller and extends into the lower part of the lesser trochanter, discriminates humans from extant great apes, except for one Gorilla . The calcar femorale was absent in one Paranthropus robustus and variably developed in all other investigated fossils. These results indicate that this structure cannot be considered as a diagnostic feature of habitual bipedal locomotion and emphasize the need for further investigations of its functional role.